Discrepancies in the rumen microbiome, metabolome, and serum metabolome among Hu sheep, East Friesian sheep, and East Friesian × Hu crossbred sheep - Du, Ruilin; Yan, Shuo; Yao, Wenna; Zhang, Huimin; Xue, Yue; Zhao, Yulong; Cao, Guifang; Liu, Jun; Zhang, Yong; Li, Xihe; Bao, Siqin; Song, Yongli (Frontiers in Microbiology, 2025)
Crossbreeding has emerged as a strategy to combine desirable traits from different sheep breeds, with the goal of enhancing productivity, disease resistance, and growth rates. This study compares the immune responses, rumen microbiomes, and serum metabolites of Hu sheep, East Friesian (EF) sheep, and crossbred Hu × EF (DH) sheep to explore the effects of crossbreeding on productivity and disease resistance. Hu sheep exhibited significantly higher lymphocyte counts (p < 0.05) and white blood cell (WBC) counts (p < 0.05) compared to EF and DH sheep, indicating stronger basal immune responses. DH sheep showed superior immune responses, with a higher cluster of differentiation 4+/cluster of differentiation 8+ (CD4+/CD8+) T cell ratio (p < 0.05) compared to EF sheep. Rumen microbiome analysis revealed distinct microbial profiles; DH sheep exhibited higher relative abundances of Prevotella (p < 0.05), which is associated with improved growth and disease resistance. Metabolomic analysis revealed significant differences in bile acid profiles: DH sheep exhibited higher levels of 6-keto lithocholic acid (6-ketoLCA), cholic acid and chenodeoxycholic acid (CDCA), and 3β-hyodeoxycholic acid (3β-HDCA) (p < 0.05), which is associated with improved immune function and gut health. These results indicate that crossbreeding improves immune resilience and metabolic efficiency, which has implications for breeding strategies designed to enhance livestock productivity and disease resistance.